Advances in Mechanism Decoupling of Cavitating Jet Impingement and Multi-Source Measurement Techniques: A Review - Ge Zhu; Bo Liu; Xiaoyu Bu; Wenjun Zhou; Yongkang Xu; Xuanjun Wang (Journal of Marine Science and Engineering, 2026)
Cavitating jet impingement is a key phenomenon in marine and ocean engineering that is responsible for cavitation-induced material erosion while also being harnessed for surface treatment applications. However, decoupling these concurrent effects is challenging since hydrodynamic jet pressure, microjet impacts, and shockwave emissions often coincide in space and time, making it difficult to isolate their individual contributions. To address this challenge, this review surveys recent advances in measurement techniques designed to decouple these overlapping effects. It highlights multi-source synchronous measurement methods, such as high-speed optical imaging and broadband piezoelectric pressure sensing combined with advanced signal and image processing, to capture mechanism-specific signatures. The review treats mechanism decoupling as a linked task of mechanism identification, mechanism attribution, and contribution quantification and synthesizes the literature under distinct criteria, such as energy, peak pressure, and damage dominance. It shows that synchronized multi-source diagnostics improve attribution reliability but that true quantitative decoupling remains limited by configuration dependence, inconsistent normalization, and a lack of benchmark evaluation criteria.